The Use of Indonesian Terms in Sports - Analis Adinda Nurwulan; Pesty Nur Annisa; Zeina Rahmana Putri; Rama Zidane Alfitra; Muhammad Fawwaz Nur Rizqy; Mochamad Whilky Rizkyanfi (Musamus Journal of Physical Education and Sport (MJPES), 2023)
Objectives. The objective of this study is to analyze the frequency of Indonesian sports-related vocabulary in contemporary sporting contexts. Sports terminology encompasses all the lexicons and phrases that delineate various aspects of athletic activities, such as techniques, regulations, and circumstances. These terminologies can either be borrowed from foreign languages like English or be indigenous to Indonesia. Some sports terminologies are generic and can be applied to multiple sports, while others are specific to particular events. In Indonesia, numerous sports-related terminologies are utilized, including athlete, division, goal, and pass. The study aims to determine the prevalence of these types of terminologies in the current sports world of Indonesia. Materials and methods. In literary inquiry, researchers rely on written sources such as books, journals, and articles as their primary data. This approach is commonly used in qualitative research and eliminates the need for researchers to conduct direct observations or interviews to gather information. Essentially, instead of engaging with subjects directly or observing their actions, researchers analyze existing written material related to the topic at hand. Results. "Using an Android-Based Sports Dictionary in Mastering Foreign Terms in the Field of Sports" written by Farid Helmi Setyawan, Puput Eka Bajuri, and published in pedagogia: educational journal in 2018. this study employed a research and Development (R&D) approach to investigate the effectiveness of an Android-based sports dictionary application in improving foreign vocabulary related to athletics. The study involved 150 participants, including students, teachers, and pupils. The results showed that 93% of the respondents were satisfied with the application, while 85% found it easier to comprehend and retain new vocabulary. The findings suggest that using an Android-based sports dictionary app can significantly enhance one's proficiency in foreign terminologies related to sports. Conclusion. The following text emphasizes the importance of using appropriate language when discussing sports in Indonesia. It highlights the significance of adhering to the rules of Indonesian language and avoiding any potential misunderstandings. Specifically, when referring to soccer, which is commonly known as football in other regions, it is crucial to modify certain English terms to ensure they are both phonetically and semantically accurate in Indonesian. The text underscores the significance of language precision in sports discussions and the need to exercise caution while selecting words to ensure clarity and comprehension